Design and Fabrication of Waste Destroying Incinerators for PT. Kujang Sakti Siliwangi - Somantri; Anggy Pradiftha Junfithrana; Dani Mardiyana; Satish Kumar Damodar (Nusa Putra University, 2024)
The rest of Cisaat Market's waste cannot be recycled by PT. Kujang Sakti Siliwangi is 2.4 tons per day while the Cimenteng TPA is almost over capacity. This causes market waste to increasingly accumulate, so a solution is needed, namely destroying waste using incinerators. The incinerator was designed using the ISO mechanical engineering drawing method using Autodesk Inventor software. The fabrication process uses methods of cutting material, welding, assembling/installing components, and painting all incinerator components. The test results are very satisfactory and the incinerator is suitable for operation because it is below the threshold according to Minister of Environment and Forestry Regulation No. 70 of 2016 concerning quality standards for emissions from businesses and/or thermal waste processing activities. The results of the Total Particulate value were 44.79 mg/Nm3, Sulfur Dioxide (SO2) was 175.70 mg/Nm3, Nitrogen Oxides (NOx) was 213.80 mg/Nm3, Hydrogen Chloride (HCl) was 5.27 mg/Nm3 , Mercury (Hg) of 0.000267 mg/Nm3, Carbon Monoxide (CO) of 85.04 mg/Nm3, Hydrogen Fluoride (HF) of 0.06 mg/Nm3.